Benefits of Bilateral Hearing on the Telephone for Cochlear Implant Recipients - Miller, Sharon; Wolfe, Jace; Duke, Mila; Schafer, Erin; Agrawal, Smita; Koch, Dawn; Neumann, Sara (Journal of the American Academy of Audiology, 2021)
Background Cochlear implant (CI) recipients frequently experience difficulty understanding speech over the telephone and rely on hearing assistive technology (HAT) to improve performance. Bilateral inter-processor audio streaming technology using nearfield magnetic induction is an advanced technology incorporated within a hearing aid or CI processor that can deliver telephone audio signals captured at one sound processor to the sound processor at the opposite ear. To date, limited data exist examining the efficacy of this technology in CI users to improve speech understanding on the telephone.Purpose The primary objective of this study was to examine telephone speech recognition outcomes in bilateral CI recipients in a bilateral inter-processor audio streaming condition (DuoPhone) compared with a monaural condition (i.e., telephone listening with one sound processor) in quiet and in background noise. Outcomes in the monaural and bilateral conditions using either a telecoil or T-Mic2 technology were also assessed. The secondary aim was to examine how deactivating microphone input in the contralateral processor in the bilateral wireless streaming conditions, and thereby modifying the signal-to-noise ratio, affected speech recognition in noise.Research Design A repeated-measures design was used to evaluate speech recognition performance in quiet and competing noise with the telephone signal transmitted acoustically or via the telecoil to the ipsilateral sound processor microphone in monaural and bilateral wireless streaming listening conditions.Study Sample Nine bilateral CI users with Advanced Bionics HiRes 90K and/or CII devices were included in the study.Data Collection and Analysis The effects of phone input (monaural [DuoPhone Off] vs. bilateral [DuoPhone on]) and processor input (T-Mic2 vs. telecoil) on word recognition in quiet and noise were assessed using separate repeated-measures analysis of variance. Effect of the contralateral device mic deactivation on speech recognition outcomes for the T-Mic2 DuoPhone conditions was assessed using paired Student's t-tests.Results Telephone speech recognition was significantly better in the bilateral inter-processor streaming conditions relative to the monaural conditions in both quiet and noise. Speech recognition outcomes were similar in quiet and noise when using the T-Mic2 and telecoil in the monaural and bilateral conditions. For the acoustic DuoPhone conditions using the T-Mic2, speech recognition in noise was significantly better when the microphone of the contralateral processor was disabled.Conclusion Inter-processor audio streaming allows for bilateral listening on the telephone and produces better speech recognition in quiet and in noise compared with monaural listening conditions for adult CI recipients.
Keywords: speech recognition; cochlear implant; noise; telephone